Приближение сопряженных периодических функций их тригармоническими интегралами Пуассона - Грабова, У.З. (Проблемы управления и информатики, 2020)
Отримано асимптотичні рівності для верхніх меж відхилень тригармонійних інтегралів Пуассона від функцій спряжених до функцій класів Гельдера в рівномірній метриці. Таким чином, розв’язано одну із найбільш важливих задач теорії наближення функцій — задачу Колмогорова–Ніколь-ського для класу і тригармонійного інтеграла Пуассона в рів-номірній метриці, що усуває прогалину в розв’язуванні даної задачі для класів спряжених періодичних функцій. Застосовано методи дослідження інтеграль-них представлень відхилень операторів, що породжуються послідовністю фун-кцій залежних від деякого неперервного параметра на класах пе-ріодичних функцій, які виникли завдяки роботам Л.І. Баусова. Класична теорія крайових задач для полігармонічних функцій стала досить добре систематизо-ваним розділом математичного моделювання. Моделювання явищ, що вивча-ються в механіці суцільних середовищ (плоска задача теорії пружності, задача вигину тонкої пластини з жорстко закріпленими краями та ін.), призводить до крайових задач для полігармонічного рівняння в певній області. Оскільки роз-виток високоточних виробництв приводить до необхідності розробки і впрова-дження асимптотичних методів теорії апроксимації, результати даної роботи можна розглядати як можливе прикладне застосування. Це пояснюється і тим, що асимптотичні методи набагато конструктивніші і простіші в обчислюваль-ній реалізації, ніж точні методи розв’язування (якщо такі взагалі існують). У реальних умовах (особливо при розробці програмного забезпечення точного машинобудування) асимптотичні методи приводять практично до тих же ре-зультатів, що і оптимальні. При подальшому вдосконаленні технологій щодо високоточного виробництва саме асимптотичним методам буде надаватися пріоритет. Цьому сприяє і розвиток наукомістких, високоточних технологій, і в останні роки досягнуто успіхів у розвитку екстремальних задач теорії на-ближення. Крім того, багато технічних задач сучасного машинобудування по-роджують нові постановки задач і в самій теорії наближення. Asymptotic equalities are obtained for the upper bounds of deviations of the three-harmonic Poisson integrals from functions conjugated to functions from the Hölder classes in the uniform metric. Thus, one of the most im-portant problems is solved in the theory of approximation of functions — the Kolmogorov–Nikol’skii problem for the class and three-harmonic Poisson integral in the uniform metric, that eliminates the gap in the solution of this problem for classes of conjugated periodic functions. In the paper the methods of investigation are used for the integral representations of deviations of operators de-fined by the sequence of functions that depend on a certain continuous parameter on the classes of periodic functions. They arose and developed due to the papers by L.I. Bausov. The classical theory of boundary problems for poly-harmonic functions became a well-organized chapter of the mathematical modeling. Modeling of phenomena studied in mechanics of continuous media (a plane prob-lem of elasticity theory, the elasticity problem of a thin plate with rigid edges etc.) leads to boundary value problems for polyharmonic equation in the specific area. Since the development of high-precision production leads to the need for develop-ment and implementation of asymptotic methods of approximation theory, then the results of this work can be considered as possible applications. This is due to the fact that asymptotic methods are much more constructive and simpler in computa-tional implementation than the exact solution methods (in case there are any). In the real conditions (especially when developing precision engineering software) as-ymptotic methods lead to almost the same results as optimal. As a result of this study, we can conclude that with further improvement of technology towards high-precision production, namely, asymptotic methods will be given a priority. This is facilitated by the development of science-intensive, high-precision technologies and the recent success in the development of extreme problems of the approxima-tion theory. In addition, a lot of technical problems of modern engineering generate new formulations of problems in the theory of approximation.